Rare bird documentation form for Glaucous Gull at Lock and Dam 19 at Keokuk, 1985 - Cecil, Robert I.et al (1985)
Rare bird documentation form for Glaucous Gull at Lock and Dam 19 at Keokuk in Lee County, IA on January 9 ,1985 and January 10, 1985. Epson - sheet feed